Colonization and antimicrobial resistance of Streptococcus pneumoniae among pediatric patients - Lusta, M.; Voronkova, O.; Shevchenko, T.; Chornyi, V.; Breus, A.; Yesaulenko, I.; Maistrenko, Y.; Shyrokykh, Y.; Falko, O. (Regulatory Mechanisms in Biosystems, 2024)
Streptococcus pneumoniae is a gram-positive microorganism that colonizes the nasopharyngeal mucosa of 30–75% of children. Samples of secretions from the nasopharynx of children suspected of having a respiratory infection were sown on Columbia agar with 5% lamb blood, incubated at a temperature of +37degrees for 18–24 hours in an atmosphere of 5% CO2. Colonies of S. pneumoniae were identified using optochin, bile disk, GP-card tests on the bacteriological analyzer VITEK 2 compact 15. Susceptibility to antibacterial drugs was determined by the disk diffusion method in accordance with European Committee on Antimicrobial Susceptibility Testing recommendations. For the period of 2021–2022, 2,578 bacteriological studies of secretions from the nasopharynx of children patients were carried out, 151 strains of S. pneumoniae were isolated (resultancy – 5.9%). The percentage of S. pneumoniae strains sensitive to oxacillin is 77.5%, norfloxacin – 88.1%, erythromycin – 49.0%, clindamycin – 63.5%, tetracycline – 45.7%, levofloxacin – 97.4%. The percentage of multi-resistant S. pneumoniae was 40.0% and 24.0% in 2021 and 2022, respectively. In 77.5% of cases, strains of S. pneumoniae are sensitive to β-lactam antibiotics, in 49.0% – to macrolides, in 63.5% – to clindamycin, in 88.1% – to fluoroquinolones, which will allow doctors to prescribe empiric antibacterial therapy for pneumococcal infections among children, with further adjustment after obtaining the antibiotic pattern of a bacteriological examination. The problem of antimicrobial resistance is only gaining publicity in the system of public health and health care, which requires the results of analyzing the spread of resistant strains and indicators of the profile of sensitivity to antimicrobial drugs. The prospects for further study lie in the further dynamic monitoring of antimicrobial resistance of S. pneumoniae among different contingents of the population.